Fabrication of epoxy modified polysiloxane with enhanced mechanical properties for marine antifouling application. (August 2019) - Sun, Xun; Chen, Rongrong; Gao, Xiang; Liu, Qi; Liu, Jingyuan; Zhang, Hongsen; Yu, Jing; Liu, Peili; Takahashi, Kazunobu; Wang, Jun
Graphical abstract: Highlights: Polysiloxane with aminopropyl-terminated pendant groups were synthesized. The synthesized polysiloxane copolymers shows higher reactivity. The mechanical properties and adhesion strength of the modified resins were improved greatly. The modified coatings exhibited excellent antifouling performance. Abstract: Marine biofouling is a catastrophic problem for maritime industries, which catches researchers' attention. Antifouling coatings have been proved to be an effective approach to against fouling organisms. Herein, we firstly synthesized polydimethylsiloxane with aminopropyl-terminated pendant groups (APDMS) through a ring opening polycondensation, and then APDMS was reacted with bisphenol A type epoxy resin (DGEBA) to form the epoxy modified polysiloxane-based resin (EAPDMS). The curing behavior of DGEBA/APDMS was studied by differential scanning calorimetry (DSC) with a non-isothermal curing method. The adhesion strength of EAPDMS was remarkably improved. The results of dynamic mechanical properties (DMA) and tensile tests showed an obvious enhancement of mechanical properties in the modified resin system. Marine field tests revealed that coatings exhibited excellent antifouling performance within 3 months. In brief, the EAPDMS coatings possess outstanding mechanical properties and excellent adhesion strength, showing high potential in the marine antifouling field.